Neonatal screening in Ukraine: development, effectiveness, prospects (Environment & Health, 2024)
The aim of the work was to evaluate the results of screening for hereditary pathology among newborns in Ukraine.Research materials and methods: data from the official statistics of the Ministry of Health of Ukraine served as materials, a systematic approach and analytical methods were used: epidemiological, probabilistic and statistical. Data from official statistics on newborn screening for VVR for the period 2010-2022 were included in the analysis.Genetic screening is an effective tool for detecting congenital metabolic disorders. Reducing the frequency of births of children with congenital and hereditary pathology is possible under the conditions of state programs aimed at reducing the impact of risk factors that cause congenital anomalies, as well as measures to prevent their occurrence. In Ukraine, mass screening of newborns began to be carried out in 1992 only at FKU. Examinations for VH were selective (indicated by the presence of a relevant anamnesis) and became mass since 2006. From 2022, examinations for 21 rare diseases will be conducted.Conclusions: During the period 2010-2022, 67.4% of newborns were tested for cystic fibrosis, 86.3% for congenital hypothyroidism, and 90.7% for phenylketonuria. Full screening coverage is predicted to identify about 335 more children with the specified diagnoses. An important condition for increasing the efficiency of state programs of neonatal screening is the widespread informing of primary care doctors and future parents about the possibilities of prevention of orphan diseases.
Keywords: screening; congenital disease; prevention